Negative electrode material and preparation method thereof, negative electrode plate and sodium ion battery

By combining WOx-W2C heterojunction nanoparticles with MXene material, a negative electrode material for sodium ion batteries was prepared, which solved the shortcomings of existing materials in terms of conductivity, kinetics and stability, and achieved high capacity and long-life battery performance.

CN119601645AActive Publication Date: 2025-03-11JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510138464.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-08
Publication Date
2025-03-11
Estimated Expiration
2045-02-08

AI Technical Summary

Technical Problem

The existing sodium ion battery anode materials have shortcomings in electronic conductivity, kinetic properties and cycle stability, which limits their reversible specific capacity and cycle stability.

Method used

The combination of WOx-W2C heterojunction nanoparticles and MXene materials was used to prepare the negative electrode material through hydrothermal and Joule heating, and the two-dimensional structure of MXene and the heterogeneous interface of WOx-W2C were used to improve the electron conductivity and ion diffusion rate.

Benefits of technology

It significantly improves the electrochemical performance of sodium ion batteries, achieves high reversible specific capacity and excellent ultra-long cycle stability, and improves the rate performance and cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601645A_ABST
    Figure CN119601645A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a negative electrode material and a preparation method thereof, a negative electrode plate and a sodium ion battery. The negative electrode material is prepared from WOx-W2C heterojunction nano particles and an MXene material, the MXene material has an accordion-shaped layered structure, and the WOx-W2C heterojunction nanoparticles are loaded on the surface of the MXene material and between the surface of the MXene material and the layered structure of the MXene material. The negative electrode material disclosed by the invention shows high reversible specific capacity and excellent super-long cycle stability, and the electrochemical performance of the sodium ion battery can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to negative electrode materials and preparation methods thereof, negative electrode sheets and sodium ion batteries. Background Art

[0002] As the global demand for sustainable energy storage solutions continues to grow, sodium-ion batteries have attracted widespread attention due to their abundant resources, low cost, and similar rocking-chair working principle to lithium-ion batteries. However, since the radius of sodium ions is larger than that of lithium ions, their diffusion rate in electrode materials is slow and may cause serious collapse of the electrode structure. Currently, a variety of carbon materials, phosphides, and sulfides have been studied as negative electrode materials for sodium-ion batteries, but they usually face problems such as poor electronic conductivity, slow kinetics, and large volume changes, which limit their reversible specific capacity and cycle stability. Therefore, it is necessary to develop a sodium-ion battery negative electrode material with excellent rate performance and cycle stability. Summary of the invention

[0003] In view of this, the present invention provides a negative electrode material and a preparation method thereof, a negative electrode sheet and a sodium ion battery. The negative electrode material exhibits high reversible specific capacity and excellent ultra-long cycle stability, and can significantly improve the electrochemical performance of the sodium ion battery.

[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: In a first aspect, the present invention provides a negative electrode material, which includes WO x -W2C heterojunction nanoparticles and MXene materials; MXene materials have an accordion-like layered structure, WO x -W2C heterojunction nanoparticles are loaded on the surface of MXene materials and between their layered structures.

[0005] Preferably, WO x -W2C heterojunction nanoparticles have an amorphous / crystalline heterointerface.

[0006] In the embodiment of the present invention, WO x -W2C heterojunction nanoparticles include tungsten oxide (WO x ) and tungsten carbide (W2C), where x is 0.5~2.

[0007] In an embodiment of the present invention, the chemical formula of the MXene material is M n+1 X n T y , wherein M is at least one of the transition metal elements Ti, V, Nb, Cr, Sc, Mo, Y, Zr, Ta, W, and Hf, X is C and / or N, T yIt is at least one of the surface functional groups -O, -Cl, -OH, and -F, and n is the number of layers, which is selected from 1, 2, or 3.

[0008] Preferably, WO x -The molar ratio of W2C heterojunction nanoparticles to MXene materials is (2-6): (4-8).

[0009] Preferably, WO x -W2C heterojunction nanoparticles, WO x The molar ratio to W2C is (1.5~5):(3.5~5).

[0010] Preferably, WO x -The crystallinity of W2C heterojunction nanoparticles is 55% to 85%.

[0011] In a second aspect, the present invention provides a method for preparing the above-mentioned negative electrode material, comprising the following steps: S1, mixing a pH adjuster, a first reducing agent and water under an inert gas atmosphere to obtain a solution A; Under an inert gas atmosphere, MXene material, tungsten source, second reducing agent and water are mixed to obtain solution B; Mixing solution A and solution B to obtain a mixed solution; Passing methane into the mixed solution to carry out a hydrothermal reaction, washing and drying the resulting precipitate to obtain a precursor C; S2, in an inert gas atmosphere, the precursor C is subjected to Joule heating to obtain amorphous WO x -W2C heterojunction nanoparticle MXene material, denoted as A-WO x -W2C / MXene.

[0012] Preferably, the molar ratio of the pH adjuster, the first reducing agent, the MXene material, the tungsten source and the second reducing agent is (1.5-3.5): (6-10): (2-4): (1-4): (0.5-2).

[0013] In an embodiment of the present invention, the pH adjuster includes at least one of sodium sulfite (Na2SO3), sodium bisulfite (NaHSO3), sodium carbonate (Na2CO3), sodium bicarbonate (NaHCO3), and acetic acid (CH3COOH).

[0014] In an embodiment of the present invention, the first reducing agent includes at least one of sodium borohydride (NaBH4), lithium aluminum hydride (LiAlH4), potassium borohydride (KBH4), and triethylsilane ((Et)3SiH).

[0015] In the embodiment of the present invention, the tungsten source includes ammonium tungstate ((NH4)2WO4), ammonium metatungstate ((NH4)6H2W 12 O 40 )、Ammonium paratungstate((NH4) 10 W 12 O 41 ), sodium tungstate (Na2WO4), potassium tungstate (K2WO4) or at least one of the following.

[0016] In an embodiment of the present invention, the second reducing agent includes at least one of hydroxylamine hydrochloride (NH2OH·HCl), sodium bisulfite (NaHSO3), ascorbic acid (C6H8O6), hydroxylamine sulfate (H8N2O6S), and hydroxylamine nitrate (NH2OH·HNO3).

[0017] Preferably, in step S1, the temperature of the hydrothermal reaction is 200-400° C., and the time of the hydrothermal reaction is 10-20 h.

[0018] Preferably, in step S2, the Joule heating treatment is carried out at a holding temperature of 1600 to 2000 K, a Joule heating treatment holding time of 3 to 8 s, and a Joule heating treatment heating rate of 800 to 1200 K s -1 .

[0019] Preferably, the preparation method further comprises step S3: in an inert gas atmosphere, x -W2C / MXene is annealed to obtain amorphous / crystalline WO x -W2C heterojunction nanoparticle MXene material, denoted as A / C-WO x -W2C / MXene.

[0020] Preferably, in step S3, the holding temperature of the annealing treatment is 300-400°C, the holding time of the annealing treatment is 3-7 h, and the heating rate of the annealing treatment is 1-5°C min -1 The cooling rate of annealing treatment is 1~5 ℃ min -1 .

[0021] In a third aspect, the present invention provides a negative electrode sheet, which comprises the above-mentioned negative electrode material and / or the negative electrode material prepared by the above-mentioned preparation method.

[0022] In a fourth aspect, the present invention provides a sodium ion battery comprising the above-mentioned negative electrode sheet.

[0023] Compared with the prior art, the present invention has the following beneficial effects: 1. The MXene material in the negative electrode material of the present invention is a new type of two-dimensional material with excellent conductivity, outstanding mechanical properties and adjustable interlayer spacing. Its layered structure serves as a conductive support, significantly enhancing electronic conductivity and limiting WO x -W2C volume change and prevents WO x -W2C powdering and attenuation. The two-dimensional structure of MXene is conducive to the rapid diffusion of ions and the effective transfer of charges, which improves the ion diffusion rate and charge and discharge performance of the battery.

[0024] 2. WO in the negative electrode material of the present invention x The surface contains abundant oxygen vacancies, defects and tungsten ions of different valence states. These characteristics make WO x To Na + It has a strong adsorption capacity. + When WO migrates from the electrolyte to the electrode surface, x It can quickly and effectively capture these ions to form a stable heterogeneous interface, thereby improving the cycle stability and rate performance of the battery; The W2C material has high conductivity, which not only provides a fast channel for electron transmission, but also enhances the overall structural stability of the composite material. This allows electrons to be quickly transmitted throughout the electrode material during the charge and discharge process, reducing resistance losses and improving energy conversion efficiency.

[0025] The present invention converts WO x When combined with W2C, the interface effect between the two will produce a large number of binding sites, which can serve as Na + adsorption center, which can also serve as a channel for electron transfer. x The difference in electronic structure between W2C and Na2C may form a built-in electric field at the interface, further promoting the + migration and embedding / ejection processes.

[0026] Moreover, the present invention can optimize the electronic structure and improve the Na + adsorption capacity; in addition, it induces a rich local built-in electric field, which significantly improves the charge transfer ability and promotes the reaction kinetics.

[0027] 3. The negative electrode material of the present invention combines WO x -W2C and MXene have complementary advantages, showing high reversible specific capacity (at 0.5 A g -1 The capacity after 500 cycles is 673.3 mA hg -1 ) and excellent ultra-long cycle stability (8 A g -1 After 10,000 cycles, the capacity is 492.4 mA hg-1 , the capacity decay per cycle is only 0.002%), which can significantly improve the electrochemical performance of sodium-ion batteries.

[0028] 4. The present invention successfully prepared the negative electrode material through hydrothermal, rapid Joule heating and annealing technology. This process effectively optimized the WO x -W2C crystallinity, which opens up a simple and effective way to improve its electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 :A / C-WO x -SEM image of W2C / MXene material (Example 1).

[0030] Figure 2 :A-WO x -TEM image of W2C / MXene material (Example 6).

[0031] Figure 3 :C-WO x -TEM image of W2C / MXene material (Example 7). DETAILED DESCRIPTION

[0032] The present invention discloses negative electrode materials and methods for preparing the same, negative electrode sheets and sodium ion batteries. Those skilled in the art can refer to the contents of this article and appropriately improve the process parameters to achieve the same. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art, and they are all deemed to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.

[0033] In the description of the present invention, it should be noted that the terms "first", "second", etc. are only used for descriptive purposes, and do not indicate or imply relative importance.

[0034] In the description of the present invention, a list of items connected by the term "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.

[0035] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range or the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0036] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0037] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0038] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0039] Specifically, the present invention adopts the following technical solutions: In a first aspect, the present invention provides a negative electrode material, which includes WO x -W2C heterojunction nanoparticles and MXene materials; MXene materials have an accordion-like layered structure, WO x -W2C heterojunction nanoparticles are loaded on the surface of MXene materials and between their layered structures.

[0040] In the present invention, the MXene material in the negative electrode material is a new type of two-dimensional material with excellent conductivity, outstanding mechanical properties and adjustable interlayer spacing. Its layered structure serves as a conductive support, significantly enhancing electronic conductivity and limiting WO x -W2C volume change and prevents WO x -W2C powdering and attenuation. The two-dimensional structure of MXene is conducive to the rapid diffusion of ions and the effective transfer of charges, which improves the ion diffusion rate and charge and discharge performance of the battery.

[0041] WO in negative electrode materials x The surface contains abundant oxygen vacancies, defects and tungsten ions of different valence states. These characteristics make WO x To Na + It has a strong adsorption capacity. + When WO migrates from the electrolyte to the electrode surface, xIt can quickly and effectively capture these ions to form a stable heterogeneous interface, thereby improving the cycle stability and rate performance of the battery; W2C material has high conductivity, which not only provides a fast channel for electron transmission, but also enhances the overall structural stability of the composite material. This allows electrons to be quickly transmitted throughout the electrode material during the charge and discharge process, reducing resistance losses and improving energy conversion efficiency. x When combined with W2C, the interface effect between the two will produce a large number of binding sites, which can serve as Na + adsorption center, which can also serve as a channel for electron transfer. x The difference in electronic structure between W2C and Na2C may form a built-in electric field at the interface, further promoting the + migration and embedding / ejection processes.

[0042] The negative electrode material of the present invention combines WO x -W2C and MXene have complementary advantages, showing high reversible specific capacity (Example 1 at 0.5 A g -1 The capacity after 500 cycles is 673.3 mA hg -1 ) and excellent ultra-long cycle stability (Example 1 at 8A g -1 After 10,000 cycles, the capacity is 492.4 mA hg -1 , the capacity decay per cycle is only 0.002%), which can significantly improve the electrochemical performance of sodium-ion batteries.

[0043] Preferably, WO x -W2C heterojunction nanoparticles have an amorphous / crystalline heterointerface. The amorphous / crystalline (A / C) heterointerface can achieve electronic structure optimization and improve Na + adsorption capacity; in addition, it induces a rich local built-in electric field, which significantly improves the charge transfer ability and promotes the reaction kinetics.

[0044] In the embodiment of the present invention, WO x -W2C heterojunction nanoparticles include tungsten oxide (WO x ) and ditungsten carbide (W2C), wherein x is 0.5 to 2. Exemplarily, x is any value among 0.5, 1, 1.5, 2 or any value within the range consisting of any two of the above values.

[0045] In an embodiment of the present invention, the chemical formula of the MXene material is M n+1 X n T y, wherein M is at least one of the transition metal elements Ti, V, Nb, Cr, Sc, Mo, Y, Zr, Ta, W, and Hf, X is C and / or N, T y It is at least one of the surface functional groups -O, -Cl, -OH, and -F, and n is the number of layers, which is selected from 1, 2, or 3.

[0046] In a specific embodiment of the present invention, the MXene material may be Ti3C2T y 、V4C3T y 、Ta4C3T y 、Nb4C3T y 、Mo2C3T y At least one of .

[0047] As a preference, WO x -W2C heterojunction nanoparticles and MXene material molar ratio is (2-6): (4-8). For example, WO x -W2C heterojunction nanoparticles and MXene material molar ratio is any value of 1:4, 3:7, 1:2, 2:3, 3:4, 1:1, 3:2 or any value within the range of any two of the above values. x -W2C heterojunction nanoparticles have a small proportion, the heterojunction effect is not significant, and at the same time, WO x -W2C nanoparticles are not added enough to modify the MXene material; when WO x When the proportion of W2C heterojunction nanoparticles is too large, WO x -W2C nanoparticles cause the overall dispersion of the material to deteriorate, affecting the uniformity and stability of the material.

[0048] As a preference, WO x -W2C heterojunction nanoparticles, WO x The molar ratio of WO to W2C is (1.5-5): (3.5-5). x The molar ratio of WO to W2C is any value among 1.5:5, 1:2, 1:1, 1.5:3.5, 5:3.5 or any value within the range of any two of the above values. x If the proportion of WO is too small, the heterojunction will not be fully formed, affecting the catalytic performance and stability of the material. x Affects the oxidation resistance of the material; when WO x When the proportion is too large, the conductivity of the material decreases, affecting the electrochemical properties of the material.

[0049] As a preference, WO x -W2C heterojunction nanoparticles have a crystallinity of 55% to 85%.x -The crystallinity of the W2C heterojunction nanoparticles is any value among 55%, 60%, 65%, 70%, 75%, 80%, 85%, or any value within the range of any two of the above values. When the crystallinity is lower than 55%, the hardness and strength of the material deteriorate; when the crystallinity is higher than 85%, the material becomes brittle and hard, reducing the toughness and plasticity of the composite material.

[0050] In a second aspect, the present invention provides a method for preparing the above-mentioned negative electrode material, comprising the following steps: S1, mixing a pH adjuster, a first reducing agent and water under an inert gas atmosphere to obtain a solution A; Under an inert gas atmosphere, MXene material, tungsten source, second reducing agent and water are mixed to obtain solution B; Mixing solution A and solution B to obtain a mixed solution; Passing methane into the mixed solution to carry out a hydrothermal reaction, washing and drying the resulting precipitate to obtain a precursor C; S2, in an inert gas atmosphere, the precursor C is subjected to Joule heating to obtain amorphous WO x -W2C heterojunction nanoparticle MXene material, denoted as A-WO x -W2C / MXene.

[0051] In step S1, under the action of a reducing agent, a tungsten source undergoes a reduction reaction to generate a low-valent oxide of tungsten (WO x ), carbide (W2C); wherein MXene participates in the reaction as a carrier or catalyst, and forms a new composite with the above reduction reaction product. x , the reaction equation of W2C is as follows: (NH4)2WO4+reducing agent→WO x (NH4)2WO4+reducing agent+CH4→W2C. (Conditions: high temperature heating) Preferably, the molar ratio of the pH adjuster, the first reducing agent, the MXene material, the tungsten source and the second reducing agent is (1.5-3.5): (6-10): (2-4): (1-4): (0.5-2). Exemplarily, the molar ratio of the pH adjuster, the first reducing agent, the MXene material, the tungsten source and the second reducing agent is any value in 2.5:10:4:1:1, 1.5:10:2:4:0.5, 3.5:6:4:1:2, 2:5:3:2:1 or any value in the range of any two of the above values.

[0052] In an embodiment of the present invention, the pH adjuster includes at least one of sodium sulfite (Na2SO3), sodium bisulfite (NaHSO3), sodium carbonate (Na2CO3), sodium bicarbonate (NaHCO3), and acetic acid (CH3COOH). Na2SO3 is preferred because Na2SO3 is relatively stable, not easy to decompose, and has a certain solubility in water, and can be conveniently used to adjust the pH value of the solution.

[0053] In an embodiment of the present invention, the first reducing agent includes at least one of sodium borohydride (NaBH4), lithium aluminum hydride (LiAlH4), potassium borohydride (KBH4), and triethylsilane ((Et)3SiH). The first reducing agent is used to reduce the tungsten-containing acid ions (e.g., WO4 2- ). NaBH4 is preferred because NaBH4 has moderate reactivity and good selectivity and can effectively reduce a variety of functional groups under mild conditions while avoiding unnecessary side reactions.

[0054] In the embodiment of the present invention, the tungsten source includes ammonium tungstate ((NH4)2WO4), ammonium metatungstate ((NH4)6H2W 12 O 40 )、Ammonium paratungstate((NH4) 10 W 12 O 41 ), sodium tungstate (Na2WO4), potassium tungstate (K2WO4). (NH4)2WO4 is preferred because (NH4)2WO4 has better reaction activity and selectivity, can better meet the process requirements, and improve the yield and purity of the product.

[0055] In an embodiment of the present invention, the second reducing agent includes at least one of hydroxylamine hydrochloride (NH2OH·HCl), sodium bisulfite (NaHSO3), ascorbic acid (C6H8O6), hydroxylamine sulfate (H8N2O6S), and hydroxylamine nitrate (NH2OH·HNO3). The above second reducing agent has strong reducing and nucleophilic properties, can participate in a variety of chemical reactions, and help promote the acid ions containing tungsten (such as WO4 2- ) and stabilize the dispersion of MXene. NH2OH·HCl is preferred because NH2OH·HCl has the characteristics of stable chemical properties, strong reducing ability, high reactivity, good solubility, and easy preparation and purification.

[0056] Preferably, in step S1, the temperature of the hydrothermal reaction is 200-400° C. Exemplarily, the temperature of the hydrothermal reaction is any value among 200° C., 250° C., 300° C., 350° C., 400° C., or any value within the range of any two of the above values.

[0057] Preferably, in step S1, the hydrothermal reaction time is 10 to 20 h. Exemplarily, the hydrothermal reaction time is any value among 10 h, 12 h, 14 h, 16 h, 18 h, 20 h, or any value within the range of any two of the above values.

[0058] Preferably, in step S2, the holding temperature of the Joule heating treatment is 1600-2000 K. Exemplarily, the holding temperature of the Joule heating treatment is any value among 1600 K, 1700 K, 1800 K, 1900 K, 2000 K or any value within the range consisting of any two of the above values.

[0059] Preferably, in step S2, the holding time of the Joule heating treatment is 3 to 8 s. Exemplarily, the holding time of the Joule heating treatment is any value among 3 s, 4 s, 5 s, 6 s, 7 s, and 8 s, or any value within the range of any two of the above values.

[0060] Preferably, in step S2, the heating rate of the Joule heating treatment is 800-1200 K s -1 For example, the heating rate of the Joule heating treatment is 800 K s -1 , 900 K s -1 , 1000 K s -1 , 1100 K s -1 , 1200 K s -1 Any value in or any value in the range consisting of any two of the above values.

[0061] Preferably, the preparation method further comprises step S3: in an inert gas atmosphere, x -W2C / MXene is annealed to obtain amorphous / crystalline WO x -W2C heterojunction nanoparticle MXene material, denoted as A / C-WO x -W2C / MXene.

[0062] Preferably, in step S3, the holding temperature of the annealing treatment is 300-400° C. Exemplarily, the holding temperature of the annealing treatment is any value among 300° C., 320° C., 340° C., 360° C., 380° C., 400° C., or any value within the range of any two of the above values.

[0063] Preferably, in step S3, the holding time of the annealing treatment is 3 to 7 h. Exemplarily, the holding time of the annealing treatment is any value among 3 h, 4 h, 5 h, 6 h, 7 h, or any value within the range of any two of the above values.

[0064] Preferably, in step S3, the heating rate of the annealing treatment is 1-5 °C min -1 For example, the heating rate of the annealing treatment is 1 °C min -1 、2℃min -1 、3℃min -1 、4℃ min -1 、5℃ min -1 Any value in or any value in the range consisting of any two of the above values.

[0065] Preferably, in step S3, the cooling rate of the annealing treatment is 1-5 °C min -1 For example, the cooling rate of the annealing treatment is 1 °C min -1 、2℃min -1 、3℃min -1 、4℃ min -1 、5℃ min -1 Any value in or any value in the range consisting of any two of the above values.

[0066] In an embodiment of the present invention, a method for preparing a MXene material includes: uniformly mixing a MAX phase material and an etching solution to obtain a mixture; stirring the mixture, collecting a precipitate, washing it, and drying it to obtain a MXene material.

[0067] In an embodiment of the present invention, the chemical formula of the MAX phase material is M n+1 AX n , wherein M is at least one of the transition metal elements Ti, V, Nb, Cr, Sc, Mo, Y, Zr, Ta, W, and Hf, A is at least one of Al, Ga, Zn, Si, P, S, Ge, As, Cd, In, Sn, Tl, and Pb, X is C and / or N elements, and n is the number of layers, which is selected from 1, 2, or 3.

[0068] In an embodiment of the present invention, the MAX phase material may be at least one of Ti3AlC2, V4AlC3, Ta4AlC3, Nb4AlC3, and Mo2AlC3.

[0069] In an embodiment of the present invention, the etching solution includes at least one of a hydrofluoric acid (HF) solution, a zinc chloride (ZnCl2) solution, a cupric chloride (CuCl2) solution, a cadmium chloride (CdCl2) solution, a hydrochloric acid (HCl) solution, a nitric acid (HNO3) solution, and a perchloric acid (HClO4) solution. HF is preferred because HF is selective in etching the MAX phase and can preferentially select the M-A bond with weaker bond energy, so that the MX layer connected by the A atoms is gradually separated to generate the corresponding MXenes material; in addition, the HF etching method has been widely used in the etching of various MAX phases.

[0070] Preferably, the mass percentage concentration of the etching solution is 20% to 60%. If the concentration range is too low (less than 20%), the etching effect is insufficient and the etching rate slows down, increasing the preparation cost and time; if the concentration is too high (greater than 60%), the etching effect is too strong, which may lead to excessive etching of MXene and destroy its crystal structure and performance. The optimal choice is 40%. When the concentration exceeds 40%, HF will begin to evaporate and form gas, which not only increases the volatility loss during the preparation process, but also may cause corrosion and pollution to the experimental environment and equipment.

[0071] In an embodiment of the present invention, the ratio of MAX phase material to etching solution is (2-5): (40-60) in g / mL.

[0072] In an embodiment of the present invention, the stirring treatment time is 12 to 24 hours to ensure that the MAX phase fully reacts with the etchant in the etching solution and is converted into a MXene material.

[0073] In a third aspect, the present invention provides a negative electrode sheet, which comprises the above-mentioned negative electrode material and / or the negative electrode material prepared by the above-mentioned preparation method.

[0074] In an embodiment of the present invention, the negative electrode sheet further includes a conductive agent and a binder. The present application does not particularly limit the types of the conductive agent and the binder, and those skilled in the art can select them according to actual needs, as long as the purpose of the present application can be achieved. The amounts of the conductive agent and the binder are conventional amounts in the art, and the present invention will not be repeated here.

[0075] In a fourth aspect, the present invention provides a sodium ion battery comprising the above-mentioned negative electrode sheet.

[0076] In the embodiment of the present invention, the battery structure includes but is not limited to button batteries, soft-pack batteries, cylindrical batteries, etc.

[0077] The present application has no particular restrictions on the positive electrode sheet, separator, and electrolyte in the battery, and those skilled in the art can select them according to actual needs as long as the purpose of the present application can be achieved.

[0078] The reagents, instruments or materials used in the present invention can be obtained through commercial channels.

[0079] The present invention will be further described below in conjunction with embodiments: Embodiment 1: The negative electrode material of this embodiment (A / C-WO x -W2C / MXene) includes the following steps: S1: First, 3 g of MAX (Ti3AlC2) powder was slowly added to 60 mL of 40% HF solution using a stepwise feeding method. Then, the mixed system was continuously stirred using a magnetic stirrer for 24 hours to ensure that MAX and HF were fully reacted and converted into MXene (Ti3C2T x ) precursor.

[0080] S2: The reaction mixture is centrifuged at 3000 rpm for 5 minutes to collect the generated MXene precipitate. The obtained precipitate needs to be washed with deionized water several times to completely remove the residual HF and other impurities. Finally, the washed MXene precipitate is dried at 60 °C for 12 hours to obtain a pure MXene product.

[0081] S3: Under argon atmosphere, 2.5 mmol of Na2SO3 powder was added to 10 mL of deionized water, and then 10 mmol of NaBH4 powder was dissolved in the above solution, named solution A.

[0082] S4: Meanwhile, 4 mmol of MXene, 1 mmol of (NH4)2WO4 and 1 mmol of NH2OH·HCl were added into 30 mL of deionized water and stirred for 2 h, named solution B.

[0083] S5: Solution A and solution B were mixed together and transferred to a 50 mL reactor, and methane gas was introduced to react at 200°C for 20 hours. The resulting precipitate was collected and washed clean with deionized water by centrifugation, and dried in a vacuum oven at 60°C for 12 hours to obtain precursor C.

[0084] S6: In a nitrogen environment, the precursor C compound is converted into A-WO by instantaneous high temperature (about 1800 K) Joule heating. x -W2C / MXene.

[0085] S7: Prepared A-WO x -W2C / MXene was placed in a quartz tube and heated at 1 °C min under argon atmosphere. -1The heating rate was raised to 300 °C and maintained for 3 h, followed by heating at 1 °C min -1 The product was named A / C-WO x -W2C / MXene.

[0086] Figure 1 It's A / C-WO x -W2C / MXene material SEM image shows that it presents a typical accordion-like structure. x -W2C / MXene composites, WO x and W2C attached between MXene sheets. It can be seen that the composite material as a whole maintains the accordion-like structure of MXene, which indicates that WO x The introduction of W2C does not destroy the two-dimensional layered structure of MXene.

[0087] Embodiment 2: The negative electrode material of this embodiment (A / C-WO x -W2C / MXene) includes the following steps: S1: First, 3 g of MAX (V4AlC3) powder was slowly added to 60 mL of 40% HF solution using a stepwise feeding method. Then, the mixed system was continuously stirred using a magnetic stirrer for 24 hours to ensure that MAX and HF were fully reacted and converted into MXene (V4C3T x ) precursor.

[0088] S2: The reaction mixture is centrifuged at 3000 rpm for 5 minutes to collect the generated MXene precipitate. The obtained precipitate needs to be washed with deionized water several times to completely remove the residual HF and other impurities. Finally, the washed MXene precipitate is dried at 60 °C for 12 hours to obtain a pure MXene product.

[0089] S3: Under argon atmosphere, 2.5 mmol of Na2SO3 powder was added to 10 mL of deionized water, and then 10 mmol of NaBH4 powder was dissolved in the above solution, named solution A.

[0090] S4: Meanwhile, 4 mmol of MXene, 1 mmol of (NH4)2WO4 and 1 mmol of NH2OH·HCl were added into 30 mL of deionized water and stirred for 2 h, named solution B.

[0091] S5: Solution A and solution B were mixed together and transferred to a 50 mL reactor, and methane gas was introduced to react at 200°C for 20 hours. The resulting precipitate was collected and washed clean with deionized water by centrifugation, and dried in a vacuum oven at 60°C for 12 hours to obtain precursor C.

[0092] S6: In a nitrogen environment, the precursor C compound is converted into A-WO by instantaneous high temperature (about 1800 K) Joule heating. x -W2C / MXene.

[0093] S7: Prepared A-WO x -W2C / MXene was placed in a quartz tube and heated at 2 °C min under argon atmosphere. -1 The heating rate was raised to 320 °C and maintained for 4 h, followed by heating at 2 °C min -1 The product was named A / C-WO x -W2C / MXene.

[0094] Embodiment 3: The negative electrode material of this embodiment (A / C-WO x -W2C / MXene) includes the following steps: S1: First, 3 g of MAX (Ta4AlC3) powder was slowly added to 60 mL of 40% HF solution using a stepwise feeding method. Then, the mixed system was continuously stirred using a magnetic stirrer for 24 hours to ensure that MAX and HF were fully reacted and converted into MXene (Ta4C3T x ) precursor.

[0095] S2: The reaction mixture is centrifuged at 3000 rpm for 5 minutes to collect the generated MXene precipitate. The obtained precipitate needs to be washed with deionized water several times to completely remove the residual HF and other impurities. Finally, the washed MXene precipitate is dried at 60 °C for 12 hours to obtain a pure MXene product.

[0096] S3: Under argon atmosphere, 2.5 mmol of Na2SO3 powder was added to 10 mL of deionized water, and then 10 mmol of NaBH4 powder was dissolved in the above solution, named solution A.

[0097] S4: Meanwhile, 4 mmol of MXene, 1 mmol of (NH4)2WO4 and 1 mmol of NH2OH·HCl were added into 30 mL of deionized water and stirred for 2 h, named solution B.

[0098] S5: Solution A and solution B were mixed together and transferred to a 50 mL reactor, and methane gas was introduced to react at 200°C for 20 hours. The resulting precipitate was collected and washed clean with deionized water by centrifugation, and dried in a vacuum oven at 60°C for 12 hours to obtain precursor C.

[0099] S6: In a nitrogen environment, the precursor C compound is converted into A-WO by instantaneous high temperature (about 1800 K) Joule heating. x -W2C / MXene.

[0100] S7: Prepared A-WO x -W2C / MXene was placed in a quartz tube and heated at 3 °C min under argon atmosphere. -1 The heating rate was raised to 340 °C and maintained for 5 h, followed by heating at 3 °C min -1 The product was named A / C-WO x -W2C / MXene.

[0101] Embodiment 4: The negative electrode material of this embodiment (A / C-WO x -W2C / MXene) includes the following steps: S1: First, 3 g of MAX (Nb4AlC3) powder was slowly added to 60 mL of 40% HF solution using a stepwise feeding method. Then, the mixed system was continuously stirred using a magnetic stirrer for 24 hours to ensure that MAX and HF were fully reacted and converted into MXene (Nb4C3T x ) precursor.

[0102] S2: The reaction mixture is centrifuged at 3000 rpm for 5 minutes to collect the generated MXene precipitate. The obtained precipitate needs to be washed with deionized water several times to completely remove the residual HF and other impurities. Finally, the washed MXene precipitate is dried at 60 °C for 12 hours to obtain a pure MXene product.

[0103] S3: Under argon atmosphere, 2.5 mmol of Na2SO3 powder was added to 10 mL of deionized water, and then 10 mmol of NaBH4 powder was dissolved in the above solution, named solution A.

[0104] S4: Meanwhile, 4 mmol of MXene, 1 mmol of (NH4)2WO4 and 1 mmol of NH2OH·HCl were added into 30 mL of deionized water and stirred for 2 h, named solution B.

[0105] S5: Solution A and solution B were mixed together and transferred to a 50 mL reactor, and methane gas was introduced to react at 200°C for 20 hours. The resulting precipitate was collected and washed clean with deionized water by centrifugation, and dried in a vacuum oven at 60°C for 12 hours to obtain precursor C.

[0106] S6: In a nitrogen environment, the precursor C compound is converted into A-WO by instantaneous high temperature (about 1800 K) Joule heating. x -W2C / MXene.

[0107] S7: Prepared A-WO x -W2C / MXene was placed in a quartz tube and heated at 4 °C min under argon atmosphere. -1 The heating rate was raised to 370 °C and maintained for 6 h, followed by sintering at 4 °C min -1 The product was named A / C-WO x -W2C / MXene.

[0108] Embodiment 5: The negative electrode material of this embodiment (A / C-WO x -W2C / MXene) includes the following steps: S1: First, 3 g of MAX (Mo2AlC3) powder was slowly added to 60 mL of 40% HF solution using a stepwise feeding method. Then, the mixed system was continuously stirred using a magnetic stirrer for 24 hours to ensure that MAX and HF were fully reacted and converted into MXene (Mo2C3T x ) precursor.

[0109] S2: The reaction mixture is centrifuged at 3000 rpm for 5 minutes to collect the generated MXene precipitate. The obtained precipitate needs to be washed with deionized water several times to completely remove the residual HF and other impurities. Finally, the washed MXene precipitate is dried at 60 °C for 12 hours to obtain a pure MXene product.

[0110] S3: Under argon atmosphere, 2.5 mmol of Na2SO3 powder was added to 10 mL of deionized water, and then 10 mmol of NaBH4 powder was dissolved in the above solution, named solution A.

[0111] S4: Meanwhile, 4 mmol of MXene, 1 mmol of (NH4)2WO4 and 1 mmol of NH2OH·HCl were added into 30 mL of deionized water and stirred for 2 h, named solution B.

[0112] S5: Solution A and solution B were mixed together and transferred to a 50 mL reactor, and methane gas was introduced to react at 200°C for 20 hours. The resulting precipitate was collected and washed clean with deionized water by centrifugation, and dried in a vacuum oven at 60°C for 12 hours to obtain precursor C.

[0113] S6: In a nitrogen environment, the precursor C compound is converted into A-WO by instantaneous high temperature (about 1800 K) Joule heating. x -W2C / MXene.

[0114] S7: Prepared A-WO x -W2C / MXene was placed in a quartz tube and heated at 5 °C min under argon atmosphere. -1 The heating rate was raised to 400 °C and maintained for 7 h, followed by 5 °C min -1 The product was named A / C-WO x -W2C / MXene.

[0115] Embodiment 6: The negative electrode material (A-WO x -W2C / MXene) includes the following steps: S1: First, 3 g of MAX powder was slowly added to 60 mL of 40% HF solution using a stepwise feeding method. Then, the mixed system was continuously stirred using a magnetic stirrer for 24 hours to ensure that MAX and HF were fully reacted and converted into MXene precursors.

[0116] S2: The reaction mixture is centrifuged at 3000 rpm for 5 minutes to collect the generated MXene precipitate. The obtained precipitate needs to be washed with deionized water several times to completely remove the residual HF and other impurities. Finally, the washed MXene precipitate is dried at 60 °C for 12 hours to obtain a pure MXene product.

[0117] S3: Under argon atmosphere, 2.5 mmol of Na2SO3 powder was added to 10 mL of deionized water, and then 10 mmol of NaBH4 powder was dissolved in the above solution, named solution A.

[0118] S4: Meanwhile, 4 mmol of MXene, 1 mmol of (NH4)2WO4 and 1 mmol of NH2OH·HCl were added into 30 mL of deionized water and stirred for 2 h, named solution B.

[0119] S5: Solution A and solution B were mixed together and transferred to a 50 mL reactor, and methane gas was introduced to react at 200°C for 20 hours. The resulting precipitate was collected and washed clean with deionized water by centrifugation, and dried in a vacuum oven at 60°C for 12 hours to obtain precursor C.

[0120] S6: In a nitrogen environment, the precursor C compound is converted into A-WO by instantaneous high temperature (about 1800 K) Joule heating. x -W2C / MXene.

[0121] Figure 2 A-WO x -TEM image of W2C / MXene material, in which an amorphous structure can be seen. This means that WO in the material x and W2C components are arranged in a disordered manner without forming an obvious crystal structure.

[0122] Embodiment 7: The negative electrode material (C-WO x -W2C / MXene) includes the following steps: S1: First, 3 g of MAX powder was slowly added to 60 mL of 40% HF solution using a stepwise feeding method. Then, the mixed system was continuously stirred using a magnetic stirrer for 24 hours to ensure that MAX and HF were fully reacted and converted into MXene precursors.

[0123] S2: The reaction mixture is centrifuged at 3000 rpm for 5 minutes to collect the generated MXene precipitate. The obtained precipitate needs to be washed with deionized water several times to completely remove the residual HF and other impurities. Finally, the washed MXene precipitate is dried at 60 °C for 12 hours to obtain a pure MXene product.

[0124] S3: Under argon atmosphere, 2.5 mmol of Na2SO3 powder was added to 10 mL of deionized water, and then 10 mmol of NaBH4 powder was dissolved in the above solution, named solution A.

[0125] S4: Meanwhile, 4 mmol of MXene, 1 mmol of (NH4)2WO4 and 1 mmol of NH2OH·HCl were added into 30 mL of deionized water and stirred for 2 h, named solution B.

[0126] S5: Solution A and solution B were mixed together and transferred to a 50 mL reactor, and methane gas was introduced to react at 200°C for 20 hours. The resulting precipitate was collected and washed clean with deionized water by centrifugation, and dried in a vacuum oven at 60°C for 12 hours to obtain precursor C.

[0127] S6: In a nitrogen environment, the precursor C compound is converted into A-WO by instantaneous high temperature (about 1800 K) Joule heating. x -W2C / MXene.

[0128] S7: Prepared A-WO x -W2C / MXene was placed in a quartz tube and sintered at 800 °C for 2 h in an argon atmosphere, and then naturally cooled to room temperature. The obtained product was named C-WO x -W2C / MXene.

[0129] Figure 3 C-WO x -TEM image of W2C / MXene material, where the crystal structure can be clearly seen. This means that the WO x And W2C components form an ordered crystal structure.

[0130] Comparative Example 1: The negative electrode material of this comparative example (A / C-WO x -W2C) includes the following steps: S1: Under argon atmosphere, 2.5 mmol of Na2SO3 powder was added to 10 mL of deionized water, and then 10 mmol of NaBH4 powder was dissolved in the above solution, named solution A.

[0131] S2: At the same time, 1 mmol (NH4)2WO4 and 1 mmol NH2OH·HCl were added to 30 mL deionized water and stirred for 2 hours, named solution B.

[0132] S3: Solution A and solution B were mixed together and transferred to a 50 mL reactor, and methane gas was introduced to react at 200°C for 20 hours. The resulting precipitate was collected and washed clean with deionized water by centrifugation, and dried in a vacuum oven at 60°C for 12 hours to obtain precursor C.

[0133] S4: In a nitrogen environment, the precursor C compound is converted into A-WO by instantaneous high temperature (about 1800 K) Joule heating. x -W2C.

[0134] S5: Prepared A-WO x -W2C was placed in a quartz tube and heated at 1 °C min in an argon atmosphere. -1 The heating rate was raised to 300 °C and maintained for 3 h, followed by heating at 1 °C min -1 The product was named A / C-WO x -W2C.

[0135] Test example: 1. Preparation of batteries: (1) Preparation of negative electrode sheet: The negative electrode sheet is prepared by using the negative electrode material prepared in the embodiment and the comparative example. The negative electrode sheet manufacturing process is as follows: the prepared negative electrode material, the conductive agent acetylene black and the binder polyvinylidene fluoride (PVDF) are mixed evenly in a ratio of 7:2:1 to form a mixture. The solvent N-methylpyrrolidone (NMP) is added to the above mixture, and stirring is continued until a uniform slurry is formed. The solid content of the slurry is 50%. The slurry is evenly coated on the current collector copper foil using a coating device, and the coating thickness is 150 nm. The coated current collector is placed in a drying device for drying.

[0136] (2) Assembly of sodium ion button half-cell: The prepared negative electrode was used as the working electrode, the metal sodium sheet was used as the reference electrode, Whatman GF / D glass fiber was used as the separator, and 1 mol L -1 100 μL of NaPF6 / DIGLYME (DIGLYME is diethylene glycol dimethyl ether, which is a solvent) was added as the electrolyte. The half-cell was assembled in the order of positive electrode shell, negative electrode sheet, diaphragm, sodium sheet, gasket, shrapnel and negative electrode shell. The assembled half-cell was clamped on the packaging machine with insulating tweezers for sealing. Finally, the packaged battery was taken out of the glove box and left to stand for 12 hours to allow the electrolyte to fully infiltrate before conducting relevant electrochemical tests.

[0137] 2. Battery performance test: (1) First-round capacity test: Take a sodium ion button half-cell and, at 26 °C, 0.5 A g -1 The first-cycle capacity test was carried out under the test conditions of current density, charge cut-off voltage of 3.0 V, and discharge cut-off voltage of 0.01 V, and the first-cycle discharge specific capacity and first-cycle coulombic efficiency were obtained.

[0138] (2) 8 A g-1 Cycle life test: Take a sodium ion button half-cell and conduct 8 A g -1 The cyclic test under the current density (charge cut-off voltage 3.0 V, discharge cut-off voltage 0.01 V) obtained 8 A g -1 Number of cycles and capacity retention at different current densities.

[0139] (3) Electrochemical impedance spectroscopy test: The electrochemical impedance spectroscopy of the sodium ion button half-cell was tested using the Letpub electrochemical workstation with a test frequency of 0.01 Hz~100 kHz to obtain the charge transfer resistance of the new battery.

[0140] (4) Constant current intermittent titration technology test: The sodium ion button half-cell was tested using the Xinwei battery testing system. A constant current intermittent titration technique test (charging cut-off voltage 3.0 V, discharging cut-off voltage 0.01 V) was performed at 26 °C to obtain the sodium ion diffusion coefficient of the new battery.

[0141] Table 1 Performance comparison of half-cells The addition of MXene in Examples 1 to 7 significantly improves the conductivity of the material and reduces the resistance of the battery. Secondly, the two-dimensional structure of MXene is conducive to the rapid diffusion of ions and the effective transfer of charges, which improves the ion diffusion rate and charge-discharge performance of the battery.

[0142] Among them, Examples 1-5, amorphous / crystalline WO x -The synergistic effect of W2C and MXene provides more active sites and a more stable structure, enabling the negative electrode material to maintain excellent performance during battery cycling.

[0143] In Example 6, due to WO x -W2C is an amorphous material. The amorphous structure leads to slightly poor structural stability, making the material more prone to structural changes during the charge and discharge cycle, and the cycle life of the battery is worse than that of Example 1-5.

[0144] In Example 7, WO x -W2C is a crystalline material, and the crystalline structure will limit the rapid diffusion of ions to a certain extent, because the diffusion path of ions in the ordered structure may be limited by the lattice. During the battery cycle, the crystalline structure may be more stable, but the repeated insertion and extraction of ions may cause fatigue and damage to the lattice to a certain extent. In terms of resistance, the conductivity of the crystalline structure is generally higher, but the resistance is also increased due to the presence of grain boundaries. The cycle life of the battery is worse than that of Example 1-6.

[0145] In Comparative Example 1, the absence of MXene will significantly reduce the conductivity of the material and increase the resistance of the battery. At the same time, as a high-performance two-dimensional conductive material, MXene can also provide structural support and stability. Its absence may cause the material to easily undergo structural changes during the battery cycle, thereby affecting the battery's cycle life. In terms of ion diffusion, the absence of MXene may also reduce the diffusion rate of ions.

[0146] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A negative electrode material, characterized in that: The negative electrode material includes WO x -W2C heterojunction nanoparticles and MXene materials; The MXene material has an accordion-like layered structure. x -W2C heterojunction nanoparticles are loaded on the surface of the MXene material and between its layered structures.

2. The negative electrode material according to claim 1, characterized in that The WO x -W2C heterojunction nanoparticles have amorphous / crystalline heterointerfaces; and / or, the WO x -W2C heterojunction nanoparticles including WO x and W2C, where x is 0.5 to 2; And / or, the chemical formula of the MXene material is M n+1 X n T y , wherein M is at least one of the transition metal elements Ti, V, Nb, Cr, Sc, Mo, Y, Zr, Ta, W, and Hf, X is C and / or N, T y It is at least one of the surface functional groups -O, -Cl, -OH, and -F, and n is the number of layers, which is selected from 1, 2, or 3.

3. The negative electrode material according to claim 1, characterized in that The WO x -The molar ratio of W2C heterojunction nanoparticles to the MXene material is (2-6): (4-8); and / or, the WO x -W2C heterojunction nanoparticles, the WO x The molar ratio of W2C is (1.5-5): (3.5-5); and / or, the WO x -The crystallinity of W2C heterojunction nanoparticles is 55% to 85%.

4. The method for preparing the negative electrode material according to any one of claims 1 to 3, characterized in that: The steps include: S1, mixing a pH adjuster, a first reducing agent and water under an inert gas atmosphere to obtain a solution A; Under an inert gas atmosphere, MXene material, tungsten source, second reducing agent and water are mixed to obtain solution B; Mixing the solution A and the solution B to obtain a mixed solution; Passing methane into the mixed solution to carry out a hydrothermal reaction, washing and drying the obtained precipitate to obtain a precursor C; S2, in an inert gas atmosphere, subjecting the precursor C to Joule heating to obtain amorphous WO x -W2C heterojunction nanoparticle MXene material, denoted as A-WO x -W2C / MXene.

5. The preparation method according to claim 4, characterized in that: The molar ratio of the pH regulator, the first reducing agent, the MXene material, the tungsten source and the second reducing agent is (1.5-3.5): (6-10): (2-4): (1-4): (0.5-2); And / or, the pH adjuster includes at least one of sodium sulfite, sodium bisulfite, sodium carbonate, sodium bicarbonate, and acetic acid; and / or, the first reducing agent comprises at least one of sodium borohydride, lithium aluminum hydride, potassium borohydride, and triethylsilane; And / or, the tungsten source includes at least one of ammonium tungstate, ammonium metatungstate, ammonium paratungstate, sodium tungstate, and potassium tungstate; And / or, the second reducing agent includes at least one of hydroxylamine hydrochloride, sodium bisulfite, ascorbic acid, hydroxylamine sulfate, and hydroxylamine nitrate.

6. The preparation method according to claim 4, characterized in that: In the step S1, the temperature of the hydrothermal reaction is 200-400° C., and the time of the hydrothermal reaction is 10-20 h; And / or, in step S2, the Joule heating treatment is carried out at a holding temperature of 1600 to 2000 K, a holding time of 3 to 8 s, and a heating rate of 800 to 1200 K s -1 .

7. The preparation method according to claim 4, characterized in that: The preparation method further comprises step S3: in an inert gas atmosphere, x -W2C / MXene is annealed to obtain amorphous / crystalline WO x -W2C heterojunction nanoparticle MXene material, denoted as A / C-WO x -W2C / MXene.

8. The preparation method according to claim 7, characterized in that: In step S3, the holding temperature of the annealing treatment is 300-400°C, the holding time of the annealing treatment is 3-7 h, and the heating rate of the annealing treatment is 1-5°C min -1 The cooling rate of the annealing treatment is 1-5 °C min -1 .

9. A negative electrode sheet, characterized in that: The negative electrode sheet comprises the negative electrode material according to any one of claims 1 to 3, and / or the negative electrode material prepared by the preparation method according to any one of claims 4 to 8.

10. A sodium ion battery, characterized in that: The sodium ion battery comprises the negative electrode sheet according to claim 9.

Citation Information

Patent Citations

  • MXene-coated WS2 heterostructure material for lithium-sulfur battery and application of MXene-coated WS2 heterostructure material

    CN114464954A

  • Application of construction of 0D / 2D / 3D defects in WO3 / MoO2 in magnesium ion battery positive electrode material

    CN115347166A

  • Preparation method of WC-WO3 heterostructure material for sulfur host of lithium-sulfur battery

    CN116873927A

  • Sodium-ion battery negative electrode material and preparation method and application thereof

    CN118099384A

  • Alkaline ion battery negative electrode material and preparation method and application thereof

    CN119349639A